2014
DOI: 10.1002/jae.2385
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Sample Trimming with Boundary Correction in Nonparametric Estimation of First‐Price Auctions

Abstract: Two-step nonparametric estimators have become standard in empirical auctions. A drawback concerns boundary effects which cause inconsistencies near the endpoints of the support and bias in finite samples. To cope, sample trimming is typically used which leads to non-random data loss. Monte Carlo experiments show this leads to poor performance near the support boundaries and on the interior due bandwidth-selection issues. We propose a modification which employs boundary-correction techniques, demonstrating subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…I use the Epanechnikov kernel function. The same correction is applied to the nonparametric estimation of first-price auction models byHickman and Hubbard (2015).…”
mentioning
confidence: 99%
“…I use the Epanechnikov kernel function. The same correction is applied to the nonparametric estimation of first-price auction models byHickman and Hubbard (2015).…”
mentioning
confidence: 99%
“…Indeed, it is observed that the R factor at the right tail of the bid distribution often has quite a large number, as it is generated by dividing a positive number by a number close to zero, tending to result in the inflated estimates of valuations. To overcome the boundary problem, Hickman and Hubbard (2015) applied the method of boundary correction to the structural asymmetric auction estimation framework. Accordingly, throughout this study, we apply the boundary correction methods for all estimates.…”
Section: Structural Estimation Methodsmentioning
confidence: 99%
“…As noted by Hickman and Hubbard (2015), boundary correction can be important in the estimation of auction models, especially if the objective is to estimate the density of valuations. The reason is that the bid distribution (in Hickman and Hubbard (2015)) or the distribution of win probabilities (here) has compact support and it is well-known that, absent a boundary correction, most nonparametric density estimators are inconsistent at the boundaries. The situation is more favorable in our case since we know that probabilities vary from zero to one whereas the top of the bid distribution must be estimated, albeit that this can be done super-consistently.…”
Section: Smoothing Transformations and Boundary Correctionmentioning
confidence: 99%